2015
DOI: 10.1021/acsami.5b04427
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Selective Sensor Chips with Graphene-Oxide Linking Layer

Abstract: The development of sensing interfaces can significantly improve the performance of biological sensors. Graphene oxide provides a remarkable immobilization platform for surface plasmon resonance (SPR) biosensors due to its excellent optical and biochemical properties. Here, we describe a novel sensor chip for SPR biosensors based on graphene-oxide linking layers. The biosensing assay model was based on a graphene oxide film containing streptavidin. The proposed sensor chip has three times higher sensitivity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 54 publications
1
84
3
Order By: Relevance
“…[91] Chen and co-workers explored an optical fiber (particularly, dual-peak long-period grating) decorated with GO and antibodies targeting anti-IgG, see Figure 5A. A 2.9-fold enhancement was discussed in this biosensing approach studied by Stebunov et al, [98] see Figure 5B. [92] In fact, the GO-coated fiber approach showed a limit of detection tenfold lower than that of the noncoated fiber.…”
Section: Go In Label-free Optical Biosensingmentioning
confidence: 99%
See 3 more Smart Citations
“…[91] Chen and co-workers explored an optical fiber (particularly, dual-peak long-period grating) decorated with GO and antibodies targeting anti-IgG, see Figure 5A. A 2.9-fold enhancement was discussed in this biosensing approach studied by Stebunov et al, [98] see Figure 5B. [92] In fact, the GO-coated fiber approach showed a limit of detection tenfold lower than that of the noncoated fiber.…”
Section: Go In Label-free Optical Biosensingmentioning
confidence: 99%
“…[90] Optical fibers are a particular example of optical waveguides. [98] In fact, GO-coated SPR substrates have been reported to outperform the bioanalytical sensitivity of commercially available biochips containing a 3D linker. The authors reported that the studied biodetection platform surpasses its counterpart without GO due to the improved chemical bonding and physical adsorption of the biorecognition enabled by GO.…”
Section: Go In Label-free Optical Biosensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous graphene-based biosensors have shown remarkable performance from diagnosis of disease to their treatment and have begun to make their way to the market place. For instance, Stebunov and co-workers 173 have demonstrated the first SPR biosensor chip by using a linked layer for biomolecule immobilization, comprising of a thin film of graphene or GO, for optical biosensing applications. The proposed biosensor chip showed good sensitivity with high binding sites and less nonspecific binding.…”
Section: Conclusion Challenges and Prospectsmentioning
confidence: 99%